Optimal Sculling Velocity Algorithms for the Gyros With Angular Rate Output - Lei Huang; Fei Xie; Kai Feng (IEEE Access, 2018)
With the advance of gyro technology, modern gyros have two output types: angular rate or integrated angular rate. However, the conventional sculling velocity algorithms usually still adopt integrated angular rate/specific-force increments as algorithm inputs. So the engineer must convert the angular rate into integrated angular rate by digital integration to use them. This step will produce non-negligible computational error. To solve this issue, we proposed two types of novel optimal sculling algorithms using angular rate input. The advantage of the novel algorithms is that they can directly calculate out the carrier velocity without converting the angular rate of gyro output into integrated angular rate. Hence, they have a higher accuracy than the conventional sculling algorithms. The results of digital simulations also demonstrate this conclusion.